Implementasi Pendidikan Perdamaian untuk Menanamkan Toleransi dan Empati pada Siswa Sekolah Dasar - Ridwan, Ridwan; Riyani, Mufti; Rahman, Aulia; Hadi Sutrisno, Imam (Program Studi Pendidikan Agama Islam, 2025)
This study aims to implement peace education in instilling tolerance and empathy values ??in Elementary Schools. This study uses a participatory and reflective School Action Research (PTS) approach. The subjects of this study were fifth grade students of Cot Keh Peureulak Elementary School, East Aceh. The sample was selected based on considerations of the need for the implementation of peace education at the grade level that is appropriate to the level of children's social and emotional development. Based on the results of the school action research conducted in two cycles, it can be concluded that peace education is effective in fostering tolerance and empathy values ??in students at Cot Keh Peureulak Elementary School, East Aceh. The learning process designed in a participatory, reflective, and contextual manner is able to create a classroom atmosphere that supports peaceful behavior and mutual respect. In cycle I, students showed low tolerance and empathy attitudes (65% and 62% respectively), while in cycle II, the score increased to 84% for tolerance and 81% for empathy. This proves that the peace education approach that is implemented in a planned and gradual manner can have a real impact on changing students' social attitudes.